Powering American farms the overlooked origins of rural electrification - Hirsh, Richard F. (Johns Hopkins University Press, 2022)
"Challenging traditional scholarship on the New Deal, the book reinterprets the history of rural electrification. It tells the previously unacknowledged story of how private power companies, with allies in land-grant universities, engendered social and technical innovations in the 1920s and early 1930s that enabled growing numbers of farmers to obtain electrical service, well before the creation of Depression-era government programs"--